2020
DOI: 10.1177/1559325820917832
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and COPD Patients’ Perception of Appropriate Metered-Dose Inhaler Technique

Abstract: Objectives: Asthma and chronic obstructive pulmonary disease (COPD) are chronic illnesses of the airways affecting a good number of people in Lebanon and the Middle East. Pressurized metered-dose inhalers (pMDIs) are important drug delivery systems used to treat such pulmonary diseases. Drugs proven to be valuable and effective may fail to act effectively if such inhalers are used incorrectly. The purpose of this study was to assess the technical use of pMDIs by patients with pulmonary diseases presenting to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Previous studies among adults mainly highlighted different factors contributing to proper inhaler technique such age, 6 gender, 7,8 education level, 7,8 using more than one inhaler, 9 receiving instructions on inhalation, 9 using metered dose inhaler (MDI), 4,6 comorbidity, 4,7 monthly income, 4 and awareness of steroid use 7 . The old study that assessed factors of proper inhaler technique among children had reported that repetition of instructions regarding inhaler use was the main determinant for correct inhaler technique 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies among adults mainly highlighted different factors contributing to proper inhaler technique such age, 6 gender, 7,8 education level, 7,8 using more than one inhaler, 9 receiving instructions on inhalation, 9 using metered dose inhaler (MDI), 4,6 comorbidity, 4,7 monthly income, 4 and awareness of steroid use 7 . The old study that assessed factors of proper inhaler technique among children had reported that repetition of instructions regarding inhaler use was the main determinant for correct inhaler technique 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also greatly affected by proper home management by parents and caregivers 11 . Only few studies have assessed the inhaler technique and its predictors among children with asthma worldwide 4,5,8,10 . Importantly, these studies were limited by their small sample size, their inclusion of other respiratory diseases, and combined population (adults and children).…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a high prevalence chronic inflammatory pulmonary disease, the respiratory symptoms of which include cough, wheezing, shortness of breath, and chest tightness which leads to elevated morbidity, mortality, and disease social and economic costs (1)(2)(3). Pulmonary inflammation is the hallmark of asthma, which is driven by a Th2 immune reponse to inhaled allergens, and associated with infiltration of the bronchial mucosa with eosinophils, CD4+ T cells, macrophages and, in exacerbations and severe cases, neutrophils (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Study found that the combination of salmeterol and fluticasone provided a significant improvement in lung mechanics in COPD patients (Chen, et al, 2016). Propriety use of MDI in asthma patients is assessed using a validated questionnaire developed by Ramadan, et al (2020). The questionnaire consists of 2 subscales with 11 questions in total.…”
Section: Resultsmentioning
confidence: 99%
“…The research instrument is a valid questionnaire to measure the proper use of MDI developed by Ramadan, et al (2020) and the Asthma Control Test (ACT) questionnaire, a standard questionnaire to measure the level of asthma control (Nathan, et al, 2004). Univariate analysis was performed to describe patients' characteristics such as age, gender, smoking habits, asthma severity, and medications used.…”
Section: Methodsmentioning
confidence: 99%